İman Olgusunun Mahiyeti ve Hakikati Üzerine Bir Değerlendirme - Şik, İsmail (Dinî araştırmalar, 2010)
This study’s aim is examination of concept of iman from the language and meaning in Kalam. Essential character of iman is tasdiq being action of heart. Tasdiq is to acceptance with information and will. However, information isn’t iman entirely on its own, information is just first degree of iman. Truth of iman is tasdiq, it is not telling with language and practising. Concept of iman in the Quran covers essential character and truth of iman.